Branding and Its Impact on Customer Loyalty in Companies (International Journal of Financial, Administrative and Economic Sciences, 2024)
The aim of this research is to study the impact of brand strength on customer loyalty, with a focus on the factors that contribute to building this loyalty. This study emphasizes that a strong brand, high quality, and effective communication are critical factors in building customer loyalty. It also asserts that a brand is not just a name or a logo, but represents the identity and values that distinguish the company in the minds of customers. Customer loyalty is considered a vital element for the sustainability and growth of companies, as it reflects the level of customer commitment to the brand and their preference for it over competitors.
Keywords: Brand; Customer Loyalty; Business